Contextualizing Greek ‘Originals’: The “Pouring Satyr” in Athens - Surtees, Allison (Actual Problems of Theory and History of Art, 2017)
The study of Greek sculpture has a long and complicated history; from Winkelmann’s ‘rise andfall’ narrative of Greek and Roman art, to Furtwängler’s hunt of Greek originals from Roman copies through the application of Kopienkritik, to the rejection of Greek context and subsequent focus on Roman contextualization of the late 20th century by parts of scholarly community. While all three views have disparate goals and approaches, all are centred on the cult of the ancient artist. This paper steps back from the question of authorship and looks towards contextualization, using the Pouring Satyr as a case study. The Pouring Satyr statue-type exists only in Roman copies and has been attributed to the 4th-century BCE sculptor Praxiteles, based primarily on literary evidence and stylistic analysis with other Roman copies. This paper re-examines the statue solely with respectto original Greek archaeological evidence connected to the statue and its identification, focusing on the pose, composition, and iconography. This analysis provides strong evidence for a putative 4th-century BCE prototype for the Roman copies. Moreover, comparison of the statue with Classical Athenian satyr iconography, almost exclusively found in vase painting, shows that the statue fits firmly into the broader satyr iconography of the 4th century. In this way, we are able to contextualize the Satyr within the known Classical Greek artistic landscape that is with respect to works firmly dated to this period. This contextualization allows us to move beyond artistic attribution and stylistic analysis, and explore the statue as an integral part of the Classical Athenian visual landscape, so that we might assign a deeper meaning for the work and for the figure of the satyr more broadly.
Keywords: Greek sculpture; Satyr; Ancient Greek art; Praxiteles; Greek pottery; Dionysus; Banquet iconography